2004
DOI: 10.1002/ps.853
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for non‐chemical weed control on public paved areas in Denmark

Abstract: To be proactive in minimizing pesticide use, the public authorities in Denmark agreed in 1998 to phase out the use of pesticides on publicly owned areas by the end of 2002. A part of the agreement was an increasing focus on research into and development of new methods and implements for non-chemical weed control on paved areas. Due to a large increase in the costs of non-chemical weed control, the park authorities have to put the different types and locations of paved areas in order of priority to optimize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 1 publication
0
35
0
2
Order By: Relevance
“…On the contrary in North Europe where the ecological awareness is much more deep-seated and where the environmental respect is closely taken into account, weed control on hard surfaces is carried out by means of non chemical treatments or by integrated management (Kortenhoff 2001;Hansen 2004;Kempenaar, 2005a;. For instance, in Sweden since 1991, about the 80% of the municipalities has approved laws that prohibited chemical weed control in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary in North Europe where the ecological awareness is much more deep-seated and where the environmental respect is closely taken into account, weed control on hard surfaces is carried out by means of non chemical treatments or by integrated management (Kortenhoff 2001;Hansen 2004;Kempenaar, 2005a;. For instance, in Sweden since 1991, about the 80% of the municipalities has approved laws that prohibited chemical weed control in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Using the model, the effects of different strategies of weed control could be estimated 9. Fig 4 shows one strategy using model parameters from Sønderborg and climate data from Sønderborg in 1999.…”
Section: Resultsmentioning
confidence: 99%
“…Fig 4 shows one strategy using model parameters from Sønderborg and climate data from Sønderborg in 1999. For a comparison of strategies see Hansen et al 9…”
Section: Resultsmentioning
confidence: 99%
“…Hansson and Ascard (2002), for example, have suggested treatment intervals of 25 days for hot water treatment on hard surface areas and Kreeb and Warnke (1994) concluded that flame treatment intervals of 2–5 weeks should be performed on railway banks to keep weed density at an acceptable level. Hansen et al. (2004) have performed experiments with different thermal methods and brushing on pavements during a 3 year period.…”
Section: Introductionmentioning
confidence: 99%
“…Flame weeding is the most commonly applied thermal weed control method on hard surfaces and is regularly used for weed control in Denmark and Sweden (Hansen et al. , 2004; Schroeder & Hansson, 2006).…”
Section: Introductionmentioning
confidence: 99%